Potential Drug–Drug Interactions in Ambulatory Patients with Hypertension: a Retrospective Study - Marcha Debby Saraswati; Shafira Muti Ardiana; Budi Suprapti; M. Yusuf Assegaf; Suharjono Suharjono; Khusnul Fitri Hamidah (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Patients with cardiovascular diseases (CVD) are vulnerable to experiencing drug-drug interactions (DDIs). DDIs are a concern among patients receiving multiple drug regimens but they are also an avoidable cause of adverse drug reactions. The study of potential DDIs (pDDIs) would make it easier for the healthcare provider to deliver better patient care and mitigate pDDIs incidence. Objective: This study aimed to assess the frequency, severity level and risk factors associated with pDDIs among medications used to treat hypertensive ambulatory patients in Universitas Airlangga hospital. Methods: A retrospective observational study was carried out from electronic prescriptions received by hypertensive patients in March 2021. Data collection includes demographic data, the profile of antihypertensive drug use, and pDDIs. pDDIs were identified by severity using Lexicomp Drug Interaction Checker (Application). Univariate logistic regression analysis was used to find associated factors of major pDDIs. A p-value less than 0.05 (â‰¤ 0.05) was considered statistically significant. Results: From 704 patients, 53.98% women and 46.02% men, 89.06% (n = 627) patients had minor to major pDDIs; 1354 pDDIs were identified, 89.4% (n = 1,210) were moderate and 9.8% (n = 133) were major class. Multiple antihypertensive drug regimens had significance associated with the major pDDIs occurrence. Conclusion: We found a high prevalence of pDDIs among hypertensive patients. The majority of pDDIs were of moderate severity. Multiple antihypertensive drug regimens were associated factors in the presence of major pDDIs.